Hubungan Breastfeeding Father dan Tingkat Pengetahuan Suami terhadap Keberhasilan Asi Eksklusif pada Ibu yang Memiliki Bayi - Marta Imelda Br Sianturi; Khairunnisa Batubara; Elvipson Sinaga; Henrianto Karolus Siregar (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Exclusive breastfeeding in Paya Mala Village, Sei Lepan District is still low. The low level of exclusive breastfeeding in Paya Mala Village, Sei Lepan District, is related to breastfeeding fathers and the husband's level of knowledge. This study aims to determine the relationship between breastfeeding father and the level of knowledge of husbands with the success of exclusive breastfeeding in mothers who have babies in the village of Paya Mala, Sei Lepan district. This type of research is analytic survey research with cross sectional design. The population in this study were all husbands of mothers who had babies in Paya Mala Village, Sei Lepan District, totaling 42 people with a total sampling of 42 people. Data collection with primary and secondary data and analyzed by chi Square statistical test with a confidence level of 95%. The results showed that there was a relationship between breastfeeding father and the success of exclusive breastfeeding in mothers who had babies in Paya Mala Village, Sei Lepan District, and there was a relationship between the husband's knowledge level and the success of exclusive breastfeeding in mothers who had babies in Paya Mala Village, Sei Lepan District. It is suggested that husbands in Paya Mala Village, Sei Lepan District, need to increase their knowledge about exclusive breastfeeding by following counseling held by health workers and seeking information about exclusive breastfeeding and for health workers in Paya Mala Village, Sei Lepan District, it is necessary to increase the understanding of mothers about exclusive breastfeeding and increase family support in an effort to increase exclusive breastfeeding.  Keywords: Breastfeeding Father, Knowledge, The Success of Exclusive Breastfeeding  ABSTRAK Pemberian ASI Eksklusif di Desa Paya Mala Kecamatan Sei Lepan masih rendah. Rendahnya pemberian ASI Eksklusif di Desa Paya Mala Kecamatan Sei Lepan terkait dengan breastfeeding father dan tingkat pengetahuan suami. Penelitian ini bertujuan untuk mengetahui hubungan breastfeeding father dan tingkat pengetahuan suami dengan keberhasilan ASI Eksklusif pada ibu yang memiliki bayi di Desa Paya Mala Kecamatan Sei Lepan. Jenis penelitian yang digunakan adalah penelitian survei analitik dengan desain cross sectional. Populasi dalam penelitian ini adalah seluruh suami dari ibu yang memiliki bayi di Desa Paya Mala Kecamatan Sei Lepan yang berjumlah 42 orang dengan total sampling sebanyak 42 orang. Pengumpulan data dengan data primer dan sekunder dan dianalisis dengan uji statistik chi Square dengan tingkat kepercayaan 95%. Hasil penelitian menunjukkan bahwa terdapat hubungan breastfeeding father dengan keberhasilan ASI Eksklusif pada ibu yang memiliki bayi di Desa Paya Mala Kecamatan Sei Lepan dan terdapat hubungan tingkat pengetahuan suami dengan keberhasilan ASI Eksklusif pada ibu yang memiliki bayi di Desa Paya Mala Kecamatan Sei Lepan. Disarankan kepada suami di Desa Paya Mala Kecamatan Sei Lepan perlu meningkatkan pengetahuan tentang pemberian ASI Eksklusif dengan mengikuti penyuluhan yang diadakan petugas kesehatan dan mencari informasi tentang ASI Ekslusif dan kepada tenaga kesehatan di Desa Paya Mala Kecamatan Sei Lepan perlu meningkatkan pemahaman ibu tentang pemberian ASI Eksklusif dan meningkatkan dukungan keluarga dalam upaya peningkatan pemberian ASI Eksklusif. Kata Kunci : Breastfeeding Father, Pengetahuan, Keberhasilan ASI Eksklusif